Child neurology practice and neurological disorders in East Africa. - Idro, R; Newton, C; Kiguli, S; Kakooza-Mwesige, A (2010)
Neurological disorders, including neurodevelopmental disorders, have been identified by the World Health Organization (WHO) as one of the greatest threats to global public health. It is generally believed that these conditions are more prevalent in the developing than the developed world because of multiple known risk factors such as infections, malnutrition, and limited resources for obstetric and neonatal management. In East Africa, few investigations have been conducted to obtain data on the magnitude and description of neurological disorders among children, and the practice of child neurology is faced with challenges cutting across areas of health personnel, patient diagnosis, management, and rehabilitation. This article reviews the burden, types, and causes of neurological disorders in the East African region. The challenges and successes in the practice of child neurology and recommendations for the future are discussed.